State of certain branches of the real sector of the economy, problems and solutions (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
Some directions of the real sector of the economy are considered. In particular, priority branches of the real sector are analyzed, such as: industry, agriculture, energy, tourism, problems and ways of their solutions are noted.
Keywords: main factors, physical volume index, growth rate, trade barriers, logistics